Pronunciation Problems of Indonesian EFL Learners in Pronouncing /g/ Sound - Febby Dwi Adeline (Fakultas Ilmu Budaya, Universitas Brawijaya, 2020)
Pronunciation is essential in delivering speech. However, pronouncing English word is difficult since the students speak Indonesian as their native language. The common problems might be caused by the differences between sound systems of the languages, especially in /g/ sound. This study objective to find how well the students’ mastery in pronouncing /g/ sound and common problems faced by them. This study highlighting two research problems; (1) how well the fourth semester students do in pronouncing /g/ sound and (2) what problems are faced by them in pronouncing /g/ sound. It is a descriptive qualitative study using triangulation data involving twenty five students of fourth semester students of English Language Education Program Faculty of Cultural Studies Universitas Brawijaya. The instruments were adapted and adopted from Dewi (2009) and developed by the researcher. The instruments are pronunciation test, recorder, assessment rubric, and questionnaire. Data analysis were done statistically and descriptively. The result of this study were (1) mostly the students’ mastery in pronouncing /g/ sound in all positions are good (81.5%) with the following details; excellent (pronouncing silent /g/ before /n/ at the end of a word, silent /g/ before /n/ in the same syllable, soft /g/ sound); good (pronouncing silent /g/ before /n/ at the beginning of a word and hard /g/ sound); average (pronouncing the exception); and poor (pronouncing silent /g/ before /m/ in the same syllable and words with /gh/ sound), (2) problems faced by the fourth semester students are the differences of sound systems between their native language and their foreign language and students’ motivation in pronouncing /g/ sound correctly (such as checking pronunciation or phonetic transcription in dictionary).